A reproducible in vitro pollen germination medium for recalcitrant cereal rye pollen (Secale cereale L): Effect of tryptone - Jayaprakash, P.; Sheeba, D.; Vikas, V. K.; Sivasamy, M.; Kumar, Jagdish; Annapoorani, S.; Krishnan, Navaneetha (The Indian Journal of Genetics and Plant Breeding, 2017)
A reproducible in vitro pollen germination medium (PGM) for cereal rye is reported here using tryptone for the first time. Rye pollen is very difficult to germinate on nutrient medium being trinucleate and is classified as recalcitrant pollen. This study addresses the possibility of testing the viability of rye pollen within short time (15-20 min) using pollen germination medium (PGM). The viability of rye pollen was tested with FDA staining also. The results of both staining and in vitro pollen germination were found comparable. In this study, tryptone, a nitrogen source was used in addition to essential sugar and inorganic salts. PGM used for rye consisted of 19% maltose, 13% poly ethylene glycol 6000, 62.5 mgl-1 boric acid, 50 mgl-1tryptone and 1% agar. During the flowering period, a pollen sterility of 3-12% was recorded. The PGM showed >93% pollen germination with intact pollen tubes at 17Â±1oC and pH 6-7. This tool would be useful in many pollen biotechnological aspects such as pollen transformation, overcoming crossability barriers especially in wheat x rye wide hybridization etc.